(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Liver controls our whole body activities. Liver cirrhosis is a most common medical problem today. One and the chief cause of it is chronic alcoholic consumption. Excessive and prolonged use of alcohol affects every organ of the body. Although liver, heart and kidney are most affected due to heavy consumption, alcohol induced liver cirrhosis is a life threatening condition in maximum cases. More than 50% people of in India rely on Ayurveda and herbal medicine for liver diseases. More than three hundred herbo-mineral preparations are available in Ayurvedic system of medicine for the treatment of jaundice and chronic liver diseases. Ayurveda plays a master role in the fast and safe recovery of damaged liver. Liver cirrhosis can be correlated to Kumbhakamala in Ayurveda w.s.r. etiology, symptoms, complications and line of treatment. Ayurvedic drugs helps in rejuvenating the liver and minimizing the complications of cirrhosis such a liver cancer, fulminant hepatitis and prevents the chronicity of the disease. In the present article, analytical review of liver disorders and its management in Ayurveda has been evaluated.